Terahertz Sensing: High‐Performance Terahertz Sensing at Exceptional Points in a Bilayer Structure (Adv. Theory Simul. 9/2018). Issue 9 (6th September 2018) - Jin, Biaobing; Tan, Wei; Zhang, Caihong; Wu, Jingbo; Chen, Jian; Zhang, Shuang; Wu, Peiheng
Abstract : In article number1800070, Biaobing Jin, Wei Tan, and co‐workers design a bilayer metasurface which is composed of two different split‐ring resonators (SRRs) on the top and bottom surfaces of an ultrathin substrate with orthogonally oriented gaps, almost identical resonance frequencies and high loss‐contrast. It is designed to possess an exceptional point. Simulations show that the sensitivity can reach 800 GHz RIU −1 μm −1, and meet the requirement of the detection of monolayer molecules at terahertz frequencies.